HUBUNGAN AKTIVITAS, STATUS EMOSIONAL DAN KUALITAS TIDUR DENGAN KUALITAS HIDUP LANSIA DI PANTI WERDHA BINA BHAKTI SERPONG TANGERANG TAHUN 2015 - Ratnawati, Diah; Riyanti, Puput (Jurnal Keperawatan Widya Gantari Indonesia, 2015)
Quality of life is one of the evaluation used to measure the level of a person's life with emphasis on an objective evaluation. Quality of life is affected by internal and external factors. internal factors are the experiences I've ever experienced before one of them is the emotional status, while external factors are all activities that dilakuakan everyday individuals like daily activities and sleep quality. This study was conducted to determine whether there is a relationship between activity, emotional status and quality of sleep and quality of life of the elderly. This study used crosssectional design, the sample used 63 respondents using purposive sampling technique. The results showed no activity relationship (P = 0.000, CI = 95%) and emotional status (0.03, CI = 95%) with the quality of life in the elderly. The results also show no relationship quality of sleep (P = 0.929, CI = 95%) with the quality of life in the elderly. Research suggests the nurse gerontik to get better at doing nursing care to the elderly, especially with regard aspects of activity and emotional status to improve the quality of life of the elderly.